Nutritional and clinical outcomes of chemoradiotherapy for clinical T1N0M0 esophageal carcinoma - Sakanaka, Katsuyuki (Cancer Manag Res, 2019)
Purpose: Whether nutritional assessment and management improves clinical outcomes in patients with clinical T1N0M0 esophageal squamous cell carcinoma (ESCC) who undergo chemoradiotherapy remains to be demonstrated. This study aimed to determine the nutritional status of such patients pre- and post-chemoradiotherapy and its clinical outcomes. Patients and methods: This single institutional retrospective study included patients who underwent chemoradiotherapy for clinical T1N0M0 ESCC using serum albumin concentrations and body weights evaluated pre- and post-chemoradiotherapy from January 2005 to December 2016. The nutritional risk index (NRI) score was used to quantify the nutritional status: NRI score ≥100: no risk, 97.5–100: mild risk, 83.5–97.5: moderate risk, and <83.5: major risk. NRI categories pre-and post-chemoradiotherapy were compared using Wilcoxon signed rank test. Local-regional control (LRC), overall survival (OS), and cause-specific survival (CSS) rates were calculated using Kaplan–Meier method. The effect of pre-chemoradiotherapy NRI score and decreased NRI category during chemoradiotherapy on OS was evaluated using log-rank test. Results: Among the 492 patients with ESCC who underwent chemoradiotherapy, 44 were included in this study. Among these, 21 patients exhibited a pre-chemoradiotherapy NRI score of <100. During chemoradiotherapy, the NRI score decreased from 100.5 to 94.5, and the median NRI category significantly decreased by 2 (p<0.0001). With a median follow-up of 72 months, the 5-year LRC, OS, and CSS rates were 79.8%, 88.9%, and 96.8%, respectively. The pre-chemoradiotherapy NRI score of <100 and decreased NRI category during chemoradiotherapy did not significantly affect OS. Conclusion: Patients with clinical T1N0M0 ESCC without dysphagia were at risk of undernutrition pre- and post-chemoradiotherapy. The current study’s results justify further clinical nutritional research for this population, and that clinicians consider nutritional support for this population.